'Unobtrusively into the ranks of colonial society': Intergenerational wealth mobility in the Cape Colony over the eighteenth century. Issue 1 (2nd January 2019) - Cilliers, Jeanne; Fourie, Johan; Swanepoel, Christie
ABSTRACT: Intergenerational mobility studies are now expanding in three directions – including different regions and time periods, using different outcomes to measure mobility, and investigating the mechanisms that affect mobility. We investigate, for the first time, wealth mobility in the Cape Colony. We compare a number of outcomes, and consider several mechanisms to explain our results. Our data allow us to match at much higher rates than before, and also include daughters. We find very high mobility at the Cape and, in contrast to the existing historiography, higher rates for those at the bottom of the wealth distribution.